Knowledge mapping of human resource analytics research: A visual analysis Using CiteSpace and VOSviewer - Mathushan, Packiyanathan; Juniarti, Atty Tri (Indonesian Journal of Sustainability Accounting and Management, 2023)
The present study aims to explore human resource analytics literature using a systematic literature review and bibliometric analysis. A sum of 179 articles extracted from the Scopus database for the years 2015–2022 with selected keywords (HR analytics, Human resource analytics, Workforce analytics, People analytics, Talent analytics, Human capital analytics) along with certain filters (subject– business, management and accounting; language-English; document–article, article in press, review articles and source-journals). Human resource analytics is discussed in this article with an emphasis on their application to human resource processes and their contribution to organisational goals. Based on the analysis, 14 influential research clusters were found: future trends, workforce analytics, talent management, human capital analytics, organisational learning, employee productivity, human resource analytics, big data challenge, adoption, evidence-based technology, recruiting, and intuition. Moreover, line managers and upper management are emphasised, making human resource analytics a strategic priority. The study presents valuable insights that aid academics and organisational practitioners in conceptualising human resource analytics practices. Additionally, this study contributes to the existing human resource analytics literature by identifying the keywords, authors, journals, and intellectual and conceptual structure.